If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2x = x + 12 Combine like terms: 4x + -2x = 2x 2x = x + 12 Reorder the terms: 2x = 12 + x Solving 2x = 12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2x + -1x = 12 + x + -1x Combine like terms: 2x + -1x = 1x 1x = 12 + x + -1x Combine like terms: x + -1x = 0 1x = 12 + 0 1x = 12 Divide each side by '1'. x = 12 Simplifying x = 12
| 42j+18-9j=-28 | | 8(x+x)=28 | | -5-2x-9=-4 | | -2(-4+8q)= | | 3(x+1)=1/81 | | 33=-11a+88 | | (-2+sqrt-8)+(5-sqrt-50)= | | 7p-3q-5q= | | 9+6x^2+x^3=0 | | X^2=x^2-6x | | 12.687*10-4= | | -2x+27=-41 | | -13=12b-b-10 | | -15m=300 | | -17a=289 | | 3a+1=-3*6(a-1) | | 2w-0.4=1+1.18w | | 450-90m=-270 | | 3x+8=9x+12 | | 26-13x=-52 | | 553/48x=265 | | -7=7/8k | | 1.5x+2=20 | | (3c-5)(3c-5)= | | -4(y+2)-6y= | | -5x+47=-31 | | -2(y+6)=y+3-(-2y) | | -180=2x+7(5x-12) | | 2x-6=3x+1-x | | -5h=85 | | 11-(-8x)+5x-(-10)= | | -3a+5+4a=10-26+5 |